Řešení defektu glenoidu kostním štěpem při implantaci reverzní totální endoprotézy ramene - operační technika a dvouleté klinické výsledky - Salus, Adam; Lena, Tomáš; Smolko, Michal (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2020)
PURPOSE OF THE STUDY The purpose of the study is to share the first experience of authors with the management of glenoid defects by a bone graft in reverse total shoulder arthroplasty. MATERIAL AND METHODS Evaluation of 7 patients was conducted, who underwent reverse total shoulder arthroplasty at the authors' department. Due to the presence of glenoid bone defect, augmentation was performed by bone graft, obtained either as an autograft harvested from the humeral head of the patient intraoperatively or as an allograft from the femoral head from the bone tissue bank. In all the implantations, a glenoid component with an extra-long "revision" peg was used. Postoperative fixation was secured only by a shoulder brace. Limited rehabilitation was commenced on the first postoperative day, full rehabilitation 5 weeks after the surgery. RESULTS The total ASES Shoulder Score increased from the mean 39.8 preoperatively to 75.2 postoperatively. Also, the overall range of motion improved, with the preoperative ventral flexion increasing from the mean 65.5° to 135.2°, abduction increasing from 63.9° preoperatively to 127.7° postoperatively, and external rotation increasing from 27.4° preoperatively to 45.1° postoperatively. In the evaluated group, 2 complications were observed, namely 1 case of bone graft breakage intraoperatively, necessitating the harvesting of a new bone graft, and 1 case of postoperative paresthesia of the fourth and the fifth finger, which completely disappeared within 4 months after the surgery. In the group of followed-up patients, no loosening of endoprosthetic components has so far been reported. DISCUSSION Glenoid defect constitutes one of the problems that need to be dealt with by the surgeon during the reverse total shoulder arthroplasty, most often it is accompanied by glenoid retroversion. The basic approach to defect management is to use the eccentric reaming technique which is, however, limited by the size of glenoid retroversion and can also worsen the already present glenoid medialization, with all the resulting consequences. Another option is to use solid bone grafts to correct glenoid version and simultaneously to lateralize the glenoid component. Yet another option is to use the prefabricated glenoid augments that are, however, not commonly available in the Czech market. CONCLUSIONS The short-term clinical outcomes of patients, in whom glenoid defect was during the reverse total shoulder arthroplasty managed by bone grafts, are very good. Radiological signs of bone-to-graph incorporation were present in all the patients of the followed-up group. Nonetheless, for the sake of evaluation of this method, more patients shall be included in the group and a longer follow-up is needed for their evaluation. Key words: reverse total shoulder arthroplasty, glenoid bone loss, glenoid retroversion, augmented implant.
Keywords: Femur Head; Scapula; artroplastika ramenního kloubu; Bone Transplantation; výsledek terapie; ramenní kloub; lidé; homologní transplantace; autologní transplantace; Treatment Outcome; lopatka; hlavice humeru; Range of Motion, Articular; retrospektivní studie; rozsah kloubních pohybů; Shoulder Joint; Humeral Head; Transplantation, Homologous; transplantace kostí; Arthroplasty, Replacement, Shoulder; hlavice femuru; Transplantation, Autologous; Retrospective Studies; Humans